KIDNEY DISEASES AND THEIR PATHOGENESIS: A SCIENTIFIC OVERVIEW - Yusupova Maftuna Azamatovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Kidney diseases encompass a broad spectrum of disorders affecting the  structure  and function of  the  kidneys.  Understanding the pathogenesis  of  these diseases  is  essential  for  effective  diagnosis,  treatment,  and  prevention.  This  article reviews common kidney diseases, including glomerulonephritis, diabetic nephropathy, and  chronic  kidney  disease  (CKD),  and  discusses  the  molecular  and  cellular mechanisms underlying their development and progression.